2012
DOI: 10.1371/journal.pone.0046478
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transhepatic Balloon Dilation of Biliary-Enteric Anastomotic Strictures after Surgical Repair of Iatrogenic Bile Duct Injuries

Abstract: PurposeTo evaluate the efficacy of percutaneous balloon dilation of biliary-enteric anastomotic strictures resulting from surgical repair of laparoscopic cholecystectomy-related bile duct injuries.Material and MethodsA total of 61 patients were referred to our institution from 1995 to 2010 for treatment of obstruction at the biliary-enteric anastomosis following surgical repair of laparoscopic cholecystectomy-related bile duct injuries. Of these 61 patients, 27 underwent surgical revision upon stricture diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…75 Percutaneous transhepatic biliary drainage followed by balloon dilation is a minimally invasive, safe, and effective option, offering the patient a quicker recovery and far less morbidity than surgery. 76 Prospective data showed that percutaneous catheter placement for 6 to 8 months in extrahepatic, single-site, biliary strictures, with progressive catheter insertion upsizing to 18F to 20F, was effective and achieved stricture resolution in 64% of patients with post-liver transplantation biliary strictures and in 86.4% of patients with BBSs with other etiologies. 77 Percutaneous transhepatic placement of retrievable covered metal stents also appeared feasible for the treatment of BBSs, with satisfied short-term or mid-term outcomes.…”
Section: Level Of Evidence: 2þþmentioning
confidence: 95%
“…75 Percutaneous transhepatic biliary drainage followed by balloon dilation is a minimally invasive, safe, and effective option, offering the patient a quicker recovery and far less morbidity than surgery. 76 Prospective data showed that percutaneous catheter placement for 6 to 8 months in extrahepatic, single-site, biliary strictures, with progressive catheter insertion upsizing to 18F to 20F, was effective and achieved stricture resolution in 64% of patients with post-liver transplantation biliary strictures and in 86.4% of patients with BBSs with other etiologies. 77 Percutaneous transhepatic placement of retrievable covered metal stents also appeared feasible for the treatment of BBSs, with satisfied short-term or mid-term outcomes.…”
Section: Level Of Evidence: 2þþmentioning
confidence: 95%
“…Anastomotic stricture is defined as a radiologically demonstrated narrowing of the biliary-enteric anastomosis associated with symptoms (jaundice, cholangitis or deranged liver function tests) requiring percutaneous, endoscopic or surgical treatment (3,29). Post-operative biliary stricture usually presented on an average period of 2.3 years (range, 0-15.3 years) after surgery, without any relationship with the nature of the primary disease (29,30).…”
Section: Bilioenteric Stricturementioning
confidence: 99%
“…The clinical success rate of PTC with balloon dilation as a first line treatment is from 66% to 87% (Table 4) (30)(31)(32)(33)(34)(35).…”
Section: Bilioenteric Stricturementioning
confidence: 99%
“…The first line of treatment is the balloon dilation first described by Molnar and Stockum 55 in 1978, a simple practice with a success rate surrounding 60% depending on the series. [56][57][58][59][60][61][62][63] The balloon dilation procedure is not a very complicated one. Over the previous biliary drainage, the guide wire advances and the withdraw of the catheter takes places.…”
Section: Benign Diseasesmentioning
confidence: 99%